Sistem Informasi Manajemen Penentuan Standar Waktu Kerja Metode Time Study Berbasis Web (Studi Kasus PT Eka Sandang Duta Prima) - Roymon Panjaitan; Myra Andriana; Tantik Sumarlin (Evolusi : Jurnal Sains dan Manajemen, 2021)
Determination of the number of workers, costs, and working time into a standard measure of the working time of a product. Time efficiency and production reports become complex issues of the importance of production timeliness. The purpose of this study is to provide a design of an information system for determining working time standards that can be accessed integrated into a more efficient report form. Methods used with research and development where data collected from observations, interviews from case studies in the field. Determination of uptime standards using time study methods developed into web-based information systems using PHP programming languages with MySQL databases. The results of the design of this study, first contribute to obtain information that can help the management in determining management policy decisions. Second, fast and accurate determination of working time standards can provide customers with answers about price and fast uptime. Third, calculating the standard time of completion of work helps to choose the best alternative working method with the principles and techniques of work measurement at PT Eka Sandang Duta Prima.